Collaboration in the formulation and implementation of policies for noncommunicable diseases in South Africa - Richard M. Rasesemola (AOSIS, 2023)
Background: Collaboration between health and other sectors is necessary and much needed when addressing health issues. The health sector alone does not possess all the necessary resources to address health problems in the country. Thus, the burden of disease because of the noncommunicable diseases (NCDs) requires interventions that are sometimes beyond the health sector's mandate. Aim: To investigate collaboration in the policy formulation process for prevention and control of NCDs in South Africa. This article presents strategies that could aid South African government to ensure collaboration by various sectors in addressing the NCDs. Setting: This study took place in the provincial Department of Health (DoH) of seven South African provinces. Methods: This was quantitative descriptive study done among purposefully sampled respondents from various health portfolios from seven provincial Departments of Health. Data were collected using questionnaires and analysed using descriptive statistical data analysis techniques. Results: The results indicated that the DoH collaborates with private and government stakeholders in the policy formulation and implementation process but excludes them in the setting the health agenda, adoption of policy options and policy evaluation. Conclusion: The lack of participation by other stakeholders in the critical phases of policy formulation will result in continued burden of disease because of poor prevention and control of NCDs in the country. Contribution: This article provides recommendations that would ensure collaboration among various sectors to accelerate the response to the prevention and control of NCDs in South Africa.